Perlindungan Konsumen Terkait Keterlambatan Pembayaran Tagihan Listrik Di Masa Pandemi Covid-19 - Sarmila Walalayo; Merry Tjoanda; Muchtar Anshary Hamid Labetubun (Faculty of Law, Universitas Pattimura, 2023)
Introduction: During the pandemic, the Ministry of Energy and Mineral Resources (ESDM) noted that household electricity and gas consumption increased by more than 30%.Purposes of the Research: The purpose of writing is to find out about the problem of how to regulate consumer protection related to delays in paying electricity account arrears due to the covid-19 pandemic and how to pay for electricity account arrears during the covid-19 pandemic.Methods of the Research: In writing this thesis the author uses the type of normative research. In this study, two approaches to the problem are used, namely the statutory approach and the conceptual approach. Sources of data obtained are primary legal materials, even secondary law, and tertiary legal materials. Techniques for collecting legal materials are collected, grouped according to their respective sections, both primary law, secondary law and tertiary law. All data from this study were analyzed qualitatively.Results of the Research: The results of this study indicate that Covid -19 is a non-natural disaster that can be categorized as a relative overmacht. Even though in this difficult condition there is still no legal basis that allows PLN to relax electricity bills, so that people as electricity consumers have an obligation to pay or pay off. bills according to the rules regulated in the Electricity Law. Consumers are required to pay electricity bills in accordance with the applicable rules, where if the consumer is late in paying electricity starting from the 1st-20th, it will be 1 month late and the customer will get a warning letter to pay it off immediately, if the customer has not paid the bill, the electricity will be refunded. Temporarily disconnected and if it is two months late the customer's electricity will be permanently cut off if the customer wants to install a new meter then the consumer is required to pay bills and fines beforehand.